2014
DOI: 10.3892/ijo.2014.2471
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA induces cytochrome c-mediated caspase cascade apoptosis in A549 human lung cancer cells via the JNK pathway

Abstract: Tanshinone IIA (TSIIA), a natural diterpene quinone in the traditional Chinese medicinal herb Dan-Shen (Salvia miltiorrhiza), has extensively exerted antitumor activity in cellular and animal models. However, the molecular mechanisms underlying the antitumor effects of TSIIA remain largely unknown. The in vitro effects of TSIIA on apoptosis were investigated in A549 non-small cell lung cancer (NSCLC) cells. The data showed that TSIIA significantly suppressed the proliferation of A549 cells in a dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 43 publications
4
27
0
Order By: Relevance
“…TSA has been demonstrated to exert an antitumor activity in numerous types of human cancer, including breast, lung, liver, prostate and ovarian cancer and leukemia (15,(21)(22)(23)(24)(25). The data of the present study showed that the exposure of the HCT1116 and COLO205 colon cancer cell lines to TSA greatly decreased their cell viability in a concentration-dependent manner (P<0.05; Fig.…”
Section: Effect Of Tsa On Cell Viability Of Colon Cancer Cellssupporting
confidence: 54%
See 1 more Smart Citation
“…TSA has been demonstrated to exert an antitumor activity in numerous types of human cancer, including breast, lung, liver, prostate and ovarian cancer and leukemia (15,(21)(22)(23)(24)(25). The data of the present study showed that the exposure of the HCT1116 and COLO205 colon cancer cell lines to TSA greatly decreased their cell viability in a concentration-dependent manner (P<0.05; Fig.…”
Section: Effect Of Tsa On Cell Viability Of Colon Cancer Cellssupporting
confidence: 54%
“…In addition, Fu et al (25) found that TSA blocked the epithelial-mesenchymal transition through the downregulation of hypoxia-inducible factor-1α, reversing hypoxia-induced chemotherapy resistance in breast cancer cell lines. In addition, increasing evidence indicated that TSA can inhibit tumor cell growth and induce apoptosis (15,17,43); however, despite the fact that in certain type of cancer evidence showed that intrinsic apoptosis pathways were involved (14,44) (46) found that TSA potentiated the efficacy of 5-FU in colon cancer cells in vivo through the downregulation of P-glycoprotein and LC3-II. The results of the present study confirmed the antitumor activity and chemosensitizing effect of TSA in colon cancer cells and provided new evidence that TSA can sensitize colon cancer cells to 5-FU through the suppression of NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…By changing the concentration of Tan I, a series of observed decaying constants of 3 Bz ⁄ and observed forming constants of 3 Tan I ⁄ were obtained. The rate constant for the excited energy transfer from 3 Bz ⁄ to Tan I is (7.61 ± 0.46) * 10 9 M À1 S À1 according to the slope, as shown in Fig.…”
Section: Energy Transfer From 3 Bz * To Tan Imentioning
confidence: 99%
“…To determine the molar absorption coefficient of 3 Tan I ⁄ , we use 3 Bz ⁄ as a reference in the energy transfer reaction [16]. The energy transfer reaction from 3 Bz ⁄ to Tan I reached its balance at approximately 1 ls after the laser pulse, as shown in Fig.…”
Section: Energy Transfer From 3 Bz * To Tan Imentioning
confidence: 99%
See 1 more Smart Citation